A kid's guide to Native American history : more than 50 activities - Dennis, Yvonne Wakim; Hirschfelder, Arlene B. (Chicago Review Press, 2010)
Hands-on activities, games, and crafts introduce children to the diversity of Native American cultures and teach them about the people, experiences, and events that have helped shape America, past and present. Nine geographical areas cover a variety of communities such as the Mohawk in the Northeast, Ojibway in the Midwest, Shoshone in the Great Basin, Apache in the Southwest, Yup'ik in Alaska, and Native Hawaiians.